Analisis Bahan Pencemar Dominan Di Muara Way Tomu Dan Muara Way Lela Wilayah Pesisir Kota Ambon - Yosias Marthen Pesulima; Pieter Kunu; Adelina Siregar (Universitas Pattimura, 2018)
The aims of this research are to find the dominant pollutants in estuarine of Way Tomu and Way Lela, determine the water quality in the estuary Way Tomu and Way Lela, and comparing the effects of the density of settlement on water quality of estuary Way Tomu and Way Lela. The research was conducted in October until November 2015. The method used was survey method with variables the physical parameters (Total Dissolved Solid, Total Suspended Solid, temperature), chemicals parameter (detergents, nitrate, nitrite, pH, BOD, COD, DO, amonia, phosphate, iron, oil and fat, manganese, coopper) and biology parameter (E. coli) class II. The result showed that the dominant chemicals parameter and affect water quality in the Way Tomu is Detergent (746 mg/L), while for the Way Lela estuary are detergent (835 mg/L), phosphate (0,4631 mg/L), and dissolved oxygen (3,2 mg/L), and biological parameters i.e., E. coli. These values have exceeded the value of the quality standard of the water quality is appropriate Government Regulation Number 82 the Year 2001 about Water Quality Management and Control of Water Pollution Classes II. It is thought to be due to the behavior of the people who live the area of the riverbanks of Way Lela and Way Tomu that their household trash into the river. For that is a need for the attention of the Government and local communities to improve the quality of the river water in the Way Tomu and Way Lela with improving the environment-friendly behavior. Keywords: pollutants, pollution estuary, way Tomu, way Lela ABSTRAK Tujuan dari penelitian ini adalah untuk menemukan polutan yang dominan di muara Way Tomu dan Way Lela; menentukan kualitas air di muara Way Tomu dan Way Lela; serta membandingkan efek dari kepadatan pemukiman terhadap kualitas air muara Way Tomu dan Way Lela. Penelitian ini telah dilakukan pada bulan Oktober sampai November 2015. Metode yang digunakan adalah metode survei dengan variabel penelitian berupa parameter fisik (Total Dissolved Solid, Total Suspended Solid, suhu), parameter kimia (deterjen, nitrat, nitrit, pH, BOD, COD, DO, amonia, fosfat, besi, minyak, dan lemak, mangan, tembaga) dan parameter biologi (E. coli) kelas II. Hasil penelitian menunjukan bahwa parameter kimia yang dominan dan mempengaruhi kualitas air di muara Way Tomu adalah Deterjen (746 mg/L) sedangkan untuk muara Way Lela adalah Deterjen (835 mg/L), Fosfat (0,4631 mg/L), dan Oksigen terlarut (3,2 mg/L), serta parameter biologi yaitu E. coli. Nilai-nilai ini telah melampaui nilai baku mutu kualitas air Sesuai Peraturan Pemerintah Nomor 82 Tahun 2001 tentang Pengelolaan Kualitas Air dan Pengendalian Pencemaran Air Kelas II. Hal ini diduga sebagai akibat perilaku masyarakat yang tinggal di daerah bantaran Way Tomu dan Way Lela yang membuang limbah rumah tangga ke sungai. Untuk itu perlu adanya perhatian pemerintah dan masyarakat setempat untuk memperbaiki kualitas air sungai di Way Tomu dan Way Lela dengan meningkatkan perilaku ramah lingkungan. Kata Kunci: bahan pencemar, pencemaran muara sungai, way Tomu, way Lela